Decision Support System In Selecting Teak Wood Raw Materials For Furniture Production At Lestari Jati - Sukmawati, Zesiy Risna Dewi; Evanita, Evanita; Riadi, Aditya Akbar (Journal La Multiapp, 2025)
The furniture industry that uses teak wood as the main raw material faces various challenges in maintaining the quality of materials and the efficiency of the production process. Teak wood is known to have advantages such as high resistance to weather and insects, good structural strength, and distinctive and elegant grain beauty. However, the quality of teak wood varies greatly depending on environmental factors, tree age, and processing process. These variations can affect the final result of furniture products, so it is important for companies to choose the right raw materials. This study aims to develop a Decision Support System (DSS) specifically designed to help Lestari Jati company in determining teak wood raw materials consistently and objectively. This DSS considers several main criteria, such as age, fiber, color, volume. The Simple Additive Weighting (SAW) method is used to give priority weight to each criterion and determine the best alternative from the available raw materials. With this system, the company is expected to be able to obtain accurate recommendations, accelerate the decision-making process, and significantly improve product quality and production efficiency, so that it can increase competitiveness in the teak wood furniture market.